Development of Android Media Based on a Realistic Approach in Blended Learning to Improve Students' Problem-Solving Skills - Ismayanty, Ismayanty; Hasratuddin, Hasratuddin; Siagian, Pargaulan (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This research aims to: (1) determine the validity, practicality, and effectiveness of Android media based on the realistic approach that was developed, (2) determine the increase in students' mathematical problem-solving skills using Android media based on the realistic approach that was developed. This research is development research. The development model used is the Plomp & Nieveen Development model which consists of three phases, namely the preliminary phase, the development or prototyping phase, and the assessment phase. Based on the results of trial I and trial II, it was found that: 1) Android media based on a realistic approach to improving students' mathematical problem-solving skills were developed which met the criteria of being valid, practical and effective; 2) Increasing problem-solving skill using Android media based on a realistic blended learning approach that has been developed as seen from the N-gain value in trial I of 0.55, increasing to 0.60 in trial II, meaning it is in the "medium" category.